Genetic and Clinical Features in 24 Chinese Distal Hereditary Motor Neuropathy Families - Xie, Yongzhi; Lin, Zhiqiang; Pakhrin, Pukar Singh; Li, Xiaobo; Wang, Binghao; Liu, Lei; Huang, Shunxiang; Zhao, Huadong; Cao, Wanqian; Hu, Zhengmao; Guo, Jifeng; Shen, Lu; et al. (Frontiers in Neurology, 2020)
Background and Objectives: Distal hereditary motor neuropathy (dHMN) is a clinically and genetically heterogeneous group of inherited neuropathies. The objectives of this study were to report the clinical and genetic features of dHMN patients in a Chinese cohort. Aims and Methods: We performed clinical assessments and whole-exome sequencing in 24 dHMN families from Mainland China. We conducted a retrospective analysis of the data and investigated the frequency and clinical features of patients with confirmed mutation. Results: Two novel heterozygous mutations c.373G>C (p.E125Q) and c.1015G>A (p.G339R) in GARS were identified and corresponded to typical dHMN-V phenotype. Together with families with WARS, SORD, SIGMAR1 and HSPB1 mutations, 29.2% of families (7/24) acquired a definite genetic diagnosis. Besides, one novel heterozygous variant of uncertain significance c.1834G>A (p.G612S) in LRSAM1 was identified in a patient with mild dHMN phenotype. Conclusion: Our study expanded the mutation spectrum of GARS mutations and added evidence that GARS mutations are associated with both axonal Charcot-Marie-Tooth and dHMN phenotypes. Mutations in genes encoding aminoamide tRNA synthetase (ARS) might be a frequent cause of autosomal dominant-dHMN, and SORD mutation might account for a majority of autosomal recessive-dHMN cases. The relatively low genetic diagnosis yield indicated more causative dHMN genes need to be discovered.